2013
DOI: 10.1590/s1519-69842013000400022
|View full text |Cite
|
Sign up to set email alerts
|

Ectoparasitic flies (Diptera, Streblidae) of bats (Chiroptera, Phyllostomidae) in an Atlantic Forest area, southeastern Brazil

Abstract: We studied infestation rates and parasite-host associations between streblid flies and phyllostomid bats in an Atlantic Forest area of Rio de Janeiro state, southeastern Brazil. We captured 301 individuals from seven Phyllostomidae bat species. Out of that total, 69 bats had been parasitised by nine Streblidae species; the most frequent species were Trichobius joblingi and Trichobius tiptoni. The species Paraeuctenodes longipes, associated with Anoura geoffroyi, was the most frequent species. The highest mean … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
8
0
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 37 publications
1
8
0
3
Order By: Relevance
“…On the other hand, studies in Brazil show a prevalence of 36.88% in São Paulo (Bertola et al, 2005), 29.90% in Pernambuco (Soares et al, 2013), 28.9% in Maranhão (Santos et al, 2009), 23% in Rio de Janeiro (França et al, 2013), and 20.12% in Rio Grande do Sul (Rui & Graciolli, 2005); while Cuxim-Koyoc et al (2015) found a prevalence of 74.06% in Yucatán-México. These differences may be related to the conditions in which the studies were conducted, variations in host and ectoparasites communities, and to different biogeographic history (Rui & Graciolli, 2005;Lourenço et al, 2016).…”
Section: Discussionmentioning
confidence: 95%
“…On the other hand, studies in Brazil show a prevalence of 36.88% in São Paulo (Bertola et al, 2005), 29.90% in Pernambuco (Soares et al, 2013), 28.9% in Maranhão (Santos et al, 2009), 23% in Rio de Janeiro (França et al, 2013), and 20.12% in Rio Grande do Sul (Rui & Graciolli, 2005); while Cuxim-Koyoc et al (2015) found a prevalence of 74.06% in Yucatán-México. These differences may be related to the conditions in which the studies were conducted, variations in host and ectoparasites communities, and to different biogeographic history (Rui & Graciolli, 2005;Lourenço et al, 2016).…”
Section: Discussionmentioning
confidence: 95%
“…Made with Natural Earth. 1 Zarazúa‐Carbajal et al (); 2 ter Hofstede et al (); 3 Durán de la Ossa et al (); 4 Tarquino‐Carbonell et al (); 5 Santos et al (); 6 Soares et al (); 7 Barbier et al (); 8 Barbier et al (); 9 Santos et al (); 10 Soares et al (); 11 Bezerra et al (); 12 Bezerra and Bocchiglieri (); 13 Rios et al (); 14 Komeno and Linhares (); 15 Azevedo and Linardi (); 16 Barbier and Graciolli (); 17 Eriksson et al (); 18 Moras et al (); 19 Dornelles et al (); 20 Graciolli et al (); 21 França et al (); 22 Lourenço et al (); 23 Almeida et al (); 24 Bertola et al (); 25 Anderson and Ortêncio‐Filho (); 26 da Silva and Ortêncio Filho (), 27 Dornelles and Graciolli (), 28 Graciolli and Bianconi (), 29 Rui and Graciolli (), 30 Camilotti et al () [Colour figure can be viewed at wileyonlinelibrary.com]…”
Section: Methodsmentioning
confidence: 99%
“…Azevedo and Linardi (2002) reported that few data about streblid flies are available in Brazil. Several studies have been published but mainly from the Atlantic Forest (França et al 2013), which is one of the five Brazilian biomes. As noted by Bertola et al (2005), several studies have been conducted on the taxonomy of Streblidae, but only a few explored host-parasite relationships.…”
mentioning
confidence: 99%